Dynamic traffic analysis model of multiple passengers for urban public transport corridor - Di Di; Yang Dongyuan (Advances in Mechanical Engineering, 2015)
For researching travel choice behavior about different kinds of passenger-alone urban public transportation corridor, a dynamic multiple-passenger flow analysis model was proposed based on dynamic equilibrium assignment theory. Some factors which might influence passenger travel disutility were considered in the model, and they were closely related to the characteristic of passenger. And then a heuristic solution algorithm is developed to solve this model. Relying on MATLAB simulation, the model could reflect the time–space distribution of multiple-passenger flow along this corridor and gave a theoretically quantitative relationship among the passenger characteristics and departure time or path/mode choice. And some useful conclusions about travel choice behavior of different passengers were obtained finally. Compared with the actual data, the deviation of the simulation results is less than 20%, which shows the efficiency of the dynamic multiple-passenger flow analysis model clearly.